2020
DOI: 10.1111/dth.13439
|View full text |Cite
|
Sign up to set email alerts
|

Do acne treatments affect insulin‐like growth factor‐1 serum levels? A clinical and laboratory study on patients with acne vulgaris

Abstract: Acne is a chronic inflammatory disease affecting sebaceous gland follicles. Lately, acne has considered an insulin‐like growth factor‐1 (IGF‐1) mediated disease. Recent research demonstrated that IGF‐1 levels decrease after 3 months of isotretinoin. The purpose of our study is evaluating the influence of acne treatments on IGF‐1 serum levels. Forty‐six subjects with acne vulgaris aged 14 to 30 years were subdivided into three groups according to their severity of acne and treated following the European Dermato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 34 publications
0
14
1
4
Order By: Relevance
“…Moreover, a significant decrease in IGF-1 concentration was demonstrated in patients treated for 3 months with isotretinoin [63]. On the other hand, in another study, it was not confirmed that anti-acne treatment, both general and local, significantly decreased IGF-1 levels [64].…”
Section: Acne Vulgarismentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, a significant decrease in IGF-1 concentration was demonstrated in patients treated for 3 months with isotretinoin [63]. On the other hand, in another study, it was not confirmed that anti-acne treatment, both general and local, significantly decreased IGF-1 levels [64].…”
Section: Acne Vulgarismentioning
confidence: 85%
“…Ponadto wykazano znaczne zmniejszenie stężenia IGF-1 u pacjentów leczonych przez 3 miesiące izotretynoiną [63]. W innym badaniu nie stwierdzono, aby leczenie przeciwtrądzikowe, zarówno ogólne, jak i miejscowe, istotnie zmniejszało stężenie IGF-1 [64].…”
Section: Conflict Of Interestunclassified
“…Karadag et al 9 in 2010 assumed and demonstrated that IGF-1 levels decreased after short-term isotretinoin treatment. Recently, Rodighiero et al have confirmed that common therapies for acne are able to modulate the systemic route of IGF-1, but not to reduce it with statistical significance 10 . Circulating levels of IGF-1 are used to evaluate the bioactivity of IGF-1 on tissue because of the lack of alternative techniques in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Rodighiero et al, 39 demonstrated that acne therapies, including oral isotretinoin, are able to modulate the systemic route of IGF‐1 bringing the suggestion that acne therapies may also be beneficial to reduce the risk of future CVD development. Further studies may confirm this suggestion 39 . Furthermore, Van et al 40 demonstrated increase in the plasma homocysteine levels after 6 to 8 week isotretinoin treatment, which did not exceed the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of development of hyperhomocysteinemia in acne patients treated with isotretinoin which is a risk factor for CVD 37,38. On the other hand, Rodighiero et al,39 demonstrated that acne therapies, including oral isotretinoin, are able to modulate the systemic route of IGF-1 bringing the suggestion that acne therapies may also be beneficial to reduce the risk of future CVD development. Further studies may confirm this suggestion 39.…”
mentioning
confidence: 99%